Pengaruh Celebrity Endorser dan E-Wom Terhadap Minat Beli dengan Brand Image Sebagai Variabel Mediasi - Irmayanti Hasan; Adam Taufiqurrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of celebrity endorsers and electronic word of mouth on purchase intention with brand image as a mediating variable. This study uses primary data by distributing questionnaires to respondents via google form to collect research data. This study uses a non-probability sampling method combined with a purposive sampling method. Data analysis in this study used the SmartPLS version 4.0 application. The findings in this study indicate that celebrity endorsers have a positive and significant effect on brand image, electronic word of mouth has a positive and significant effect on brand image, celebrity endorsers have a positive and significant effect on purchase intention, electronic word of mouth has a positive and significant effect on purchase intention, brand image has a positive and significant effect on purchase intention. brand image can have a direct and significant effect on the relationship between celebrity endorser variables on purchase intention, brand image can have a direct and significant effect on the relationship between electronic word of mouth variables on purchase intention.